Industrial relations: Bibliometric analysis approach (Lighthouse Publishing, 2023)
Industrial relations are an important part of business organization, providing broad social benefits. However, ethics in industrial relationships can become a problem. In Scandinavia and Switzerland, various types of business organizations, chambers of industry and commerce, chambers of commerce, and employers' associations are joined. Further research is needed due to the wide scope of the topic and lack of systematic literature review. This study aims to identify broadly the keywords of industrial relations and findings that are relevant to current conditions. This research is meant to contribute to future research. This research method uses a bibliometric analysis approach using the VOSviewer application and a search for research articles using the Publish or Perish (PoP) application from 2013-2023 with a total of 200 articles and explains in detail the 10 most cited articles. The research results are submitted in the form of co-authorship, co-occurrence, citations, and keywords related to industrial relations, namely university-industry collaboration, digitalization, industry 4.0, innovation, and others.